GLOBAL FOOD SECURITY PROBLEMS - Aliyev Abdukadir Kamoliddin ogli (Bright Mind Publishing, 2025)
Food security is a major global issue, increasingly urgent due to population growth, climate change, and limited agricultural resources. This article analyzes the basic principles of food security, global problems, causes and consequences, and ways to solve them. It also discusses the problems that arise in the processes of food production, supply, and consumption.
Keywords: Food security, global problems, agriculture, climate change, resources, supply, food policy.